Amphiphilic ionic functionalized MOF zinc acrylate polymer coating for marine antifouling and method of preparation thereof

CN122978787APending Publication Date: 2026-10-27JIANGSU SOBUTE NEW MATERIALS CO LTD +1
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202611476268.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-09-22
Publication Date
2026-10-27

AI Technical Summary

Benefits of technology

工艺简化:避免了两性离子配体的复杂合成步骤,利用商业化氨基MOF和两性离子化试剂即可制备;

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The application discloses a kind of amphiprotic ion functionalized MOF zinc acrylate polymer coating for marine antifouling and a preparation method thereof, including zinc acrylate polymer 30-50 parts by weight, supported amphiprotic ion functionalized MOF material 5-20 parts, solid filler 20-40 parts, functional additive 1-2 parts and organic solvent 15-30 parts.The coating of the application introduces amphiprotic ion functionalized MOF filler into zinc acrylate self-polishing resin system, utilizes the self-polishing characteristics of zinc acrylate to realize dynamic updating of coating surface, utilizes the hydration layer effect of amphiprotic ion to resist initial adhesion of microorganisms, utilizes the pore structure of MOF to realize intelligent controlled release of antifouling agent, forming a technical solution of synergistic effect of "self-polishing updating-anti-adhesion-controlled release" triple antifouling mechanism.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of antifouling coating technology, specifically relating to an amphoteric functionalized MOF zinc acrylate polymer coating for marine antifouling and its preparation method. Background Technology

[0002] Marine biofouling is one of the major challenges facing marine engineering worldwide. Facilities such as ships, offshore platforms, and seawater pipelines that are submerged in seawater for extended periods are highly susceptible to the attachment and growth of marine bacteria, diatoms, barnacles, mussels, and other organisms. This leads to increased navigation resistance, higher fuel consumption, and accelerated metal corrosion, resulting in significant economic losses and safety hazards.

[0003] Self-polishing antifouling coatings are currently the most widely used marine antifouling technology. Among them, zinc acrylate resin has become the mainstream base material for self-polishing antifouling coatings due to its excellent hydrolytic self-polishing performance and environmental protection characteristics. Zinc acrylate resin slowly hydrolyzes in seawater through ion exchange reaction, continuously releasing antifouling agents and renewing the coating surface, thereby achieving long-term antifouling. However, traditional zinc acrylate antifouling coatings still have the following problems: (1) The release rate of antifouling agents is difficult to control precisely, and the initial burst release and insufficient release in the later stage lead to limited antifouling effect; (2) The coating surface is prone to adsorbing proteins and microbial mucus, which accelerates biofouling; (3) The use of antifouling agents such as high content of cuprous oxide brings environmental risks; (4) A single antifouling mechanism is difficult to cope with the complex and ever-changing marine fouling biological community.

[0004] In recent years, metal-organic frameworks (MOFs) have shown great potential in the field of antifouling loading and controlled release due to their ultra-high specific surface area, tunable pore structure, and ease of functionalization. Studies have shown that MOFs can serve as nanocarriers for antifouling agents, enabling the slow release of antifouling agents such as cuprous oxide and isothiazolinones, avoiding explosive release problems. For example, Chinese patent CN115141508B discloses an antifouling agent supported on a carboxyl-functionalized MOF containing a quaternary ammonium salt of a benzisothiazolinone derivative and its preparation method, achieving the slow release of the antifouling agent. However, MOF materials themselves lack resistance to protein adsorption, and their stability in aquatic environments needs improvement.

[0005] Zwitterionic materials, due to the presence of both positively and negatively charged groups within their molecules, can form a dense hydration layer through hydration, effectively resisting the adhesion of proteins and microorganisms, making them a research hotspot for antifouling coatings. However, zwitterionic coatings typically lack sufficient mechanical strength and the ability to actively kill attached organisms.

[0006] To address the shortcomings of existing technologies, this invention provides a MOF-zwitterionic modified zinc acrylate polymer marine antifouling coating to solve the aforementioned problems. Summary of the Invention

[0007] The purpose of this invention is to provide a zwitterionic functionalized MOF zinc acrylate polymer coating for marine antifouling and its preparation method. By introducing zwitterionic functionalized MOF fillers into the zinc acrylate self-polishing resin system, the self-polishing properties of zinc acrylate are used to achieve dynamic renewal of the coating surface. The hydration layer effect of zwitterionic ions is used to resist the initial adhesion of microorganisms. The porous structure of MOF is used to achieve intelligent controlled release of antifouling agents, forming a technical solution with a synergistic effect of a triple antifouling mechanism of "self-polishing renewal - anti-adhesion - controlled release", thereby solving the problems mentioned in the background art.

[0008] To achieve the above objectives, the present invention provides the following technical solution: an amphoteric functionalized MOF zinc acrylate polymer coating for marine antifouling, comprising, by weight, parts of... The ingredients are: 30-50 parts zinc acrylate polymer, 5-20 parts supported zwitterionic functionalized MOF material, 20-40 parts solid filler, 1-2 parts functional additives, and 15-30 parts organic solvent.

[0009] Preferably, the zinc acrylate polymer is an acrylic copolymer with zinc ester side chains, having an acid value of 50-200 mg KOH / g and a zinc content of 2-15 wt%.

[0010] Preferably, in any of the above embodiments, the zinc acrylate polymer is prepared by solution polymerization or bulk polymerization of acrylic acid, acrylates (such as methyl acrylate, butyl acrylate, isooctyl acrylate, etc.) and zinc-containing monomers (such as zinc acrylate, zinc methacrylate).

[0011] In any of the above embodiments, it is preferred that the solid filler includes any one or a combination of one or more of titanium dioxide, talc, barium sulfate, heavy calcium carbonate, light calcium carbonate, zinc oxide, mica powder, bentonite, and iron oxide red.

[0012] Preferably, in any of the above embodiments, the functional additive includes one or a combination of wetting and dispersing agents and defoamers.

[0013] Preferably, in any of the above embodiments, the organic solvent includes any one or a combination of more than one of xylene, toluene, ethyl acetate, butyl acetate, and methyl isobutyl ketone.

[0014] Preferably, in any of the above embodiments, the preparation process of the supported zwitterionic functionalized MOF material is as follows: The impregnation adsorption method was used to disperse zwitterionic functionalized MOFs with a mass ratio of 1:5-20 in an antifouling additive solution with a concentration of 1-20 mg / mL, and the mixture was stirred for 6-24 hours to allow the antifouling additive molecules to diffuse into the MOF pores. Centrifugation was performed, and the antifouling agent adsorbed on the surface of the above zwitterionic functionalized MOF was washed with anhydrous solvent. The MOF was then vacuum dried at 60°C to constant weight to obtain the supported zwitterionic functionalized MOF material.

[0015] Among them, antifouling additives include any one or more of cuprous oxide, copper pyridinethione, zinc pyridinethione, benzisothiazolinone, and 4,5-dichloro-2-n-octyl-4-isothiazolin-3-one.

[0016] Preferably, in any of the above embodiments, the antifouling agent solution is formed by dissolving and dispersing any one or more of cuprous oxide, copper pyridinethione, zinc pyridinethione, benzisothiazolinone, and 4,5-dichloro-2-n-octyl-4-isothiazolin-3-one in ethanol.

[0017] Preferably, in any of the above schemes, the preparation process of the zwitterionic functionalized MOF is as follows: Amino-functionalized MOF and zwitterionic reagent are dispersed in anhydrous solvent, wherein the mass ratio of amino-functionalized MOF, zwitterionic reagent and anhydrous solvent is 1:1-10:50-200, and the reaction is carried out at 40-100℃ for 12-48 hours. After the reaction was completed, the mixture was centrifuged, washed thoroughly with anhydrous solvent 3-5 times to remove unreacted reagents, and dried under vacuum at 40-80℃ to obtain zwitterionic functionalized MOFs.

[0018] The metal ions in MOF are selected from zirconium (Zr). 4+ ), copper (Cu²) + ), Zinc (Zn²) + ), titanium (Ti 4+ The organic ligands of MOF are selected from one or more of 2-aminoterephthalic acid, 2,5-dihydroxyterephthalic acid, and pyromellitic acid.

[0019] Preferably, in any of the above schemes, the amino-functionalized MOF includes any one or a combination of more than one of UiO-66-NH2, MIL-101-NH2, and NH2-MIL-125.

[0020] The zwitterion groups are derived from any one or more of sulfobetaine compounds, carboxybetaine compounds, or amino acid compounds.

[0021] Preferably, in any of the above embodiments, the zwitterionic reagent includes any one or a combination of more than one of 1,3-propanesulfonate lactone, 1,4-butanesulfonate lactone, or glycidyltrimethylammonium chloride.

[0022] Preferably, in any of the above embodiments, the anhydrous solvent includes one or a combination of DMF (N,N-dimethylformamide) and ethanol.

[0023] This invention also includes a method for preparing zwitterionic functionalized MOF zinc acrylate polymer coatings for marine antifouling, comprising the following steps: The supported zwitterionic functionalized MOF material, zinc acrylate polymer, organic solvent, solid filler and functional additives are sequentially placed into a reaction vessel and stirred evenly for 2-5 hours, and then filtered to obtain the coating.

[0024] Based on the above technical solution, the following improvements are summarized: 1. Covalent bonding structure of zwitterions with MOFs In existing technologies, the recombination of zwitterions with MOFs often employs non-covalent methods such as physical mixing or ion exchange. However, zwitterions are prone to desorption from the MOF surface, leading to functional degradation. This invention grafts zwitterion groups onto the MOF framework via covalent bonding. Specifically: The -NH2 group of amino-functionalized MOFs (such as UiO-66-NH2, MIL-101-NH2) can undergo a ring-opening reaction with sulfonate lactone zwitterions to form a stable sulfonate-ammonium zwitterion structure. The zwitterions are firmly connected to the MOF framework through covalent bonds, avoiding the problem of easy dissolution of zwitterions in physical mixing methods, and significantly improving the long-term stability of the functional layer. Covalent grafting ensures the uniform distribution of zwitterions on the inner wall and surface of MOF channels, forming a continuous and dense antifouling hydration layer.

[0025] 2. Gradient structure of MOF core-zwitterionic shell This invention constructs a gradient functional structure of MOF core-zwitterionic shell: MOF core layer: Maintaining the original high specific surface area, ordered pore structure and antifouling agent loading capacity of MOF, serving as a nano reservoir for antifouling agents; Amphoteric shell: A dense zwitterionic layer is formed on the surface of MOF and the inner wall of the pores, giving the material superhydrophilicity and resistance to protein adsorption. Gradient interface: The zwitterionic layer and the MOF framework are connected by covalent bonds to form a continuous transition interface structure, which avoids the core-shell separation problem; This core-shell gradient structure achieves an organic unity between the loading function of MOF and the anti-adhesion function of zwitterions, overcoming the defect of the two functions being separated in the prior art.

[0026] 3. Synergistic effect of the "anti-adhesion-controlled release-self-renewal" triple antifouling mechanism Existing technologies mostly rely on a single antifouling mechanism, which is insufficient to cope with complex marine fouling environments. This invention is the first to integrate a triple antifouling mechanism into the same coating system, as shown in Table 1: Table 1: 4. Synergistic effect of the three mechanisms Sequential Synergy: The anti-adhesion mechanism dominates the antifouling function in the early stage of coating application, blocking initial fouling; as the coating hydrolyzes, the controlled-release mechanism is gradually activated, releasing antifouling agents to kill attached organisms; the self-renewal mechanism operates throughout the process, continuously renewing the coating surface; Spatial synergy: Zwitterionic functionalized MOFs are uniformly dispersed in zinc acrylate resin, functioning simultaneously on the coating surface and within the coating itself. The surface zwitterionic layer resists fouling adhesion, while the internal MOF stores antifouling agents ready for release. Complementary functions: The anti-adhesion mechanism compensates for the defect of easy protein adsorption in the self-polishing coating before renewal; the controlled release mechanism compensates for the lack of active killing function of zwitterions; and the self-renewal mechanism solves the problem of easy contamination of MOFs after long-term exposure.

[0027] 5. Confined loading of antifouling agent in MOF channels In existing technologies, antifouling agents are mostly added directly to coatings through physical dispersion or loaded onto the surface of fillers through simple adsorption. This has the disadvantages of low loading capacity and rapid release. This invention uses an impregnation adsorption method to load the antifouling agent into the nanopores of zwitterionic functionalized MOFs: Pore ​​confinement effect: The nanopores of MOF (with a pore size of typically 0.5-2 nm) have a spatial confinement effect on antifouling agent molecules, restricting their free diffusion and enabling slow release; High loading capacity: Utilizing the high specific surface area of ​​MOF (up to 800-1200 m² / g), high-efficiency loading of antifouling agents can be achieved (loading capacity can reach 20-30 wt%). Molecular sieving effect: The pore size selectivity of MOF allows only small molecule antifouling agents to enter, while excluding large molecule contaminants and protecting the antifouling agents in the pores from contamination.

[0028] 6. Intelligent release mechanism in response to zwitterions This invention further utilizes the intelligent response characteristics of zwitterions to achieve responsive regulation of antifouling agent release: pH response: zwitterionic groups (such as sulfonic acid groups and ammonium groups) can undergo charge transitions under different pH conditions. When microbial metabolism causes local pH changes, the conformation and hydrophilicity / hydrophobicity of zwitterions change, triggering the release of antifouling agents. Ion strength response: The difference in hydration capacity of zwitterions in high-salt seawater environments can regulate the diffusion rate of antifouling agents from MOF channels. Microbial response: When microorganisms begin to attach, their metabolites can trigger conformational changes in zwitterions, accelerating the local release of antifouling agents and achieving intelligent antifouling with "on-demand release". This intelligent release mechanism ensures that the antifouling agent is released only when needed, avoiding ineffective release and resource waste, and significantly extending the antifouling effectiveness period.

[0029] 7. Zwitterionic modification improves the interfacial compatibility between MOF and resin. In the prior art, MOF fillers tend to agglomerate in organic resin matrices, affecting coating performance. This invention significantly improves the interfacial compatibility between MOF and zinc acrylate resin through zwitterionic modification. Surface energy matching: The introduction of zwitterionic layer modulates the surface energy of MOF, making it closer to the surface energy of zinc acrylate resin, thus reducing interfacial tension; Hydrogen bonding interaction: Zwitterionic groups (sulfonic acid group, ammonium group) can form hydrogen bonds with the ester group and carboxyl group of zinc acrylate resin, which enhances the interfacial bonding force; Steric hindrance stability: The zwitterionic layer forms a steric hindrance layer on the MOF surface, which hinders the aggregation between MOF particles and improves dispersion stability.

[0030] 8. Functional additive synergistic dispersion system This invention constructs a stable dispersion system through the synergistic effect of functional additives (wetting and dispersing agents) and zwitterionic functionalized MOFs: The wetting and dispersing agent is adsorbed on the MOF surface and forms a composite stable layer with the zwitterionic layer, further enhancing the steric hindrance effect; The amphiphilic structure of the dispersant can interact with both the MOF surface and the resin matrix simultaneously, acting as a "bridging" mechanism to promote the uniform dispersion of MOF in the resin. By optimizing the type and amount of dispersant, the MOF filler is monodispersed, thus avoiding coating defects caused by agglomeration.

[0031] 9. Amphoteric ion protective layer enhances the water stability of MOFs The structural stability of MOFs in aquatic environments is a key issue restricting their marine applications. This invention significantly enhances the water stability of MOFs through zwitterionic modification: Hydrophobic barrier: The dense structure of the zwitterionic layer can block water molecules from entering the MOF framework, thus slowing down the hydrolysis reaction rate; Framework reinforcement: Secondary interactions (such as hydrogen bonding and electrostatic interactions) between zwitterions and MOF metal clusters or ligands can reinforce the MOF framework and inhibit structural collapse.

[0032] 10. Self-polishing and renewal mechanism ensures long-lasting activity. This invention utilizes the self-polishing properties of zinc acrylate resin to achieve continuous renewal of the coating surface: As the coating surface hydrolyzes, the zwitterionic functionalized MOFs exposed on the surface are continuously renewed, avoiding contamination and deactivation caused by long-term immersion; The self-polishing rate can be precisely controlled by adjusting the acid value (50-200 mgKOH / g) and zinc content (2-15wt%) of the zinc acrylate resin to meet the needs of different sea areas and application scenarios.

[0033] 11. Process optimization of post-modification method This invention employs a post-modification method to graft zwitterions onto amino-functionalized MOFs, which has the following advantages compared to the one-step coordination method: Simplified process: It avoids the complex synthesis steps of zwitterionic ligands and can be prepared using commercially available amino MOFs and zwitterionic reagents; High versatility: Applicable to a variety of amino-functionalized MOFs (UiO-66-NH2, MIL-101-NH2, NH2-MIL-125), different MOF supports can be selected according to application requirements; Grafting rate is controllable: By adjusting the reaction temperature (40-100℃), time (12-48 hours), and amount of zwitterionic reagent, the grafting rate of zwitterions (0.5-2.5 mmol / g) can be precisely controlled.

[0034] 12. Integrated process of antifouling agent loading and MOF modification This invention integrates zwitterionic modification and antifouling agent loading into a continuous process: First, zwitterionic modification is performed, and then the modified MOF is used to load the antifouling agent, thus avoiding the influence of the zwitterionic modification process on the loaded antifouling agent. The pore structure of MOF remains intact after zwitterionic modification, and the BET specific surface area retention rate is >85%, providing ample space for antifouling agent loading. The loading process uses the immersion adsorption method, which is mild (room temperature) and simple to operate, making it suitable for large-scale production.

[0035] The technical effects and advantages of this invention are as follows: 1. Triple pollution prevention and control mechanism Self-polishing and renewal: The ion exchange reaction of zinc acrylate resin in seawater causes continuous hydrolysis of the coating surface, constantly releasing antifouling agents and renewing the coating surface, effectively removing attached fouling organisms and achieving dynamic antifouling; Anti-adhesion hydration layer: The zwitterionic functionalized MOF surface has zwitterionic groups such as sulfonic acid group and ammonium group, which form a dense hydration layer on the coating surface through electrostatic interaction and hydration, resisting the initial adhesion of proteins, bacteria and diatoms. Intelligent controlled release of antifouling agents: The nanopores of zwitterionic functionalized MOFs have a confinement effect on antifouling agents, enabling slow release of antifouling agents through diffusion control; at the same time, the pH-responsive characteristics of zwitterions enable intelligent response release of antifouling agents.

[0036] 2. Synergistic effect of MOF-zwitterion-zinc acrylate Amphoteric functionalized MOFs, as nanofillers, are uniformly dispersed in a zinc acrylate resin matrix, which not only enhances the mechanical properties of the coating but also imparts anti-adhesion functionality to the coating. As the zinc acrylate resin hydrolyzes, the zwitterionic functionalized MOF exposed on the coating surface continues to exert its anti-adhesion effect, while releasing the loaded antifouling additives. MOF's high specific surface area and porous structure enable efficient loading and slow release of antifouling additives, solving the problem of uncontrollable release rates in traditional antifouling coatings.

[0037] 3. Long-lasting anti-fouling and environmentally friendly properties The antifouling agent is loaded into the MOF channels to avoid initial explosive release and extend the antifouling effectiveness. The zwitterionic groups are biocompatible materials, reducing the amount of highly toxic antifouling agents used and lowering environmental risks; The coating's self-polishing properties allow the coating surface to continuously renew itself, preventing fouling organisms from adhering firmly. Detailed Implementation

[0038] The technical solutions in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0039] The sources of the raw materials used in this invention are shown in Table 2. Table 2: Example 1: First, zwitterionic functionalized MOFs were prepared, and the specific process is as follows: 1g of UiO-66-NH2 and 5g of 1,3-propanesulfonate lactone were dispersed in 100g of ethanol and reacted at 60°C for 12 hours. After the reaction was completed, the mixture was centrifuged, washed five times with ethanol to remove unreacted reagents, and dried under vacuum at 60°C to obtain zwitterionic functionalized MOFs.

[0040] Secondly, the supported zwitterionic functionalized MOF material was prepared, and the specific process is as follows: 1 g of zwitterionic functionalized MOF was dispersed in 10 g of cuprous oxide solution (concentration 10 mg / mL) and stirred for 12 hours to allow the antifouling agent molecules to diffuse into the MOF channels. Centrifugation was performed, and the cuprous oxide adsorbed on the surface was washed with ethanol. The material was then vacuum dried at 60°C to obtain a zwitterionic functionalized MOF material.

[0041] Finally, the zwitterionic functionalized MOF zinc acrylate polymer coating was prepared, and the specific process is as follows: Take 300g of zinc acrylate polymer, 100g of supported zwitterionic functionalized MOF material, 150g of xylene, 100g of n-butanol, 60g of zinc oxide, 100g of light calcium carbonate, 10g of titanium dioxide, 100g of talc, 20g of bentonite, 50g of iron oxide red, 5g of wetting and dispersing agent and 5g of defoamer and put them into a clean reactor in sequence. Stir evenly at 2000r / min and filter after 3h to obtain zwitterionic functionalized MOF zinc acrylate polymer coating for marine antifouling.

[0042] Example 2: First, zwitterionic functionalized MOFs were prepared, and the specific process is as follows: 1g of MIL-101-NH2 and 1g of 1,4-butanesulfonate lactone were dispersed in 50g of DMF and reacted at 40°C for 24 hours. After the reaction was completed, the mixture was centrifuged, washed three times with ethanol to remove unreacted reagents, and dried under vacuum at 40°C to obtain zwitterionic functionalized MOFs.

[0043] Secondly, the supported zwitterionic functionalized MOF material was prepared, and the specific process is as follows: 1 g of zwitterionic functionalized MOF was dispersed in 5 g of 4,5-dichloro-2-n-octyl-4-isothiazolin-3-one solution (concentration 1 mg / mL) and stirred for 6 hours to allow the antifouling agent molecules to diffuse into the MOF channels. Centrifugation was performed, and the surface adsorbed 4,5-dichloro-2-n-octyl-4-isothiazolin-3-one was washed with DMF. The mixture was then vacuum dried at 60°C to obtain the supported zwitterionic functionalized MOF packing.

[0044] Finally, the zwitterionic functionalized MOF zinc acrylate polymer coating was prepared, and the specific process is as follows: Take 300g of zinc acrylate polymer, 200g of supported zwitterionic functionalized MOF material, 150g of xylene, 150g of n-butanol, 100g of light calcium carbonate, 50g of talc, 10g of bentonite, 40g of iron oxide red, 5g of wetting and dispersing agent and 5g of defoamer and put them into a clean reactor in sequence. Stir evenly at 2000r / min and filter after 2h to obtain zwitterionic functionalized MOF zinc acrylate polymer coating for marine antifouling.

[0045] Example 3: First, zwitterionic functionalized MOFs were prepared, and the specific process is as follows: 1 g of NH2-MIL-125 and 10 g of glycidyltrimethylammonium chloride were dispersed in 200 g of ethanol and reacted at 100 °C for 48 hours. After the reaction was completed, the mixture was centrifuged, washed five times with ethanol to remove unreacted reagents, and dried under vacuum at 80°C to obtain zwitterionic functionalized MOFs.

[0046] Secondly, the supported zwitterionic functionalized MOF material was prepared, and the specific process is as follows: 1 g of zwitterionic functionalized MOF was dispersed in 20 g of zinc pyrithione solution (concentration 20 mg / mL) and stirred for 24 hours to allow the antifouling agent molecules to diffuse into the MOF pores. Centrifugation was performed, and the zinc pyridinethione adsorbed on the surface was washed with ethanol. The mixture was then vacuum dried at 60°C to obtain the supported zwitterionic functionalized MOF packing.

[0047] Finally, the zwitterionic functionalized MOF zinc acrylate polymer coating was prepared, and the specific process is as follows: Take 350g of zinc acrylate polymer, 100g of supported zwitterionic functionalized MOF material, 200g of xylene, 150g of n-butanol, 100g of heavy calcium carbonate, 10g of titanium dioxide, 100g of barium sulfate, 10g of bentonite, 20g of iron oxide red, 5g of wetting and dispersing agent and 5g of defoamer and put them into a clean reactor in sequence. Stir evenly at 2000r / min and filter after 5h to obtain zwitterionic functionalized MOF zinc acrylate polymer coating for marine antifouling.

[0048] Example 4: First, zwitterionic functionalized MOFs were prepared, and the specific process is as follows: 3g of UiO-66-NH2, 2g of MIL-101-NH2 and 30g of 1,3-propanesulfonate lactone were dispersed in 200g of ethanol and 300g of DMF and reacted at 60°C for 24 hours. After the reaction was completed, the mixture was centrifuged, washed five times with ethanol to remove unreacted reagents, and dried under vacuum at 60°C to obtain zwitterionic functionalized MOFs.

[0049] Secondly, the supported zwitterionic functionalized MOF material was prepared, and the specific process is as follows: 5 g of zwitterionic functionalized MOF was dispersed in 100 g of copper pyridinethione solution (concentration 15 mg / mL) and stirred for 24 hours to allow the antifouling agent molecules to diffuse into the MOF channels. After centrifugation, the adsorbed copper pyridinethione on the surface was washed with ethanol and dried under vacuum at 60 °C to obtain the supported zwitterionic functionalized MOF filler.

[0050] Finally, the zwitterionic functionalized MOF zinc acrylate polymer coating was prepared, and the specific process is as follows: Take 450g of zinc acrylate polymer, 100g of supported zwitterionic functionalized MOF material, 100g of xylene, 100g of n-butanol, 50g of zinc oxide, 50g of light calcium carbonate, 10g of titanium dioxide, 100g of talc, 10g of bentonite, 20g of iron oxide red, 5g of wetting and dispersing agent and 5g of defoamer and put them into a clean reactor in sequence. Stir evenly at 2000r / min and filter after 3h to obtain zwitterionic functionalized MOF zinc acrylate polymer coating for marine antifouling.

[0051] Example 5: First, zwitterionic functionalized MOFs were prepared, and the specific process is as follows: 100g of UiO-66-NH2 and 600g of 1,3-propanesulfonate lactone were dispersed in 2000g of ethanol and reacted at 70°C for 24 hours. After the reaction was completed, the mixture was centrifuged, washed five times with ethanol to remove unreacted reagents, and dried under vacuum at 60°C to obtain zwitterionic functionalized MOFs.

[0052] Secondly, the supported zwitterionic functionalized MOF material was prepared, and the specific process is as follows: 100g of zwitterionic functionalized MOF was dispersed in 500g of cuprous oxide solution (concentration 10 mg / mL) and 1000g of zinc pyrithione solution (concentration 20 mg / mL), and stirred for 12 hours to allow the antifouling agent molecules to diffuse into the MOF channels. Centrifugation was performed, and the adsorbed cuprous oxide and zinc pyridinethione on the surface were washed with ethanol. The mixture was then vacuum dried at 60°C to obtain the supported zwitterionic functionalized MOF packing.

[0053] Finally, the zwitterionic functionalized MOF zinc acrylate polymer coating was prepared, and the specific process is as follows: Take 400g of zinc acrylate polymer, 100g of supported zwitterionic functionalized MOF material, 50g of xylene, 100g of n-butanol, 50g of zinc oxide, 100g of barium sulfate, 100g of titanium dioxide, 50g of talc, 10g of bentonite, 20g of iron oxide red, 8g of wetting and dispersing agent and 12g of defoamer and put them into a clean reactor in sequence. Stir evenly at 2000r / min and filter after 3h to obtain zwitterionic functionalized MOF zinc acrylate polymer coating for marine antifouling.

[0054] Example 6: First, zwitterionic functionalized MOFs were prepared, and the specific process is as follows: 1g of UiO-66-NH2, 2g of 1,3-propanesulfonate lactone, and 3g of glycidyltrimethylammonium chloride were dispersed in 100g of ethanol and reacted at 60°C for 24 hours. After the reaction was completed, the mixture was centrifuged, washed five times with ethanol to remove unreacted reagents, and dried under vacuum at 60°C to obtain zwitterionic functionalized MOFs.

[0055] Secondly, the supported zwitterionic functionalized MOF material was prepared, and the specific process is as follows: 1 g of zwitterionic functionalized MOF was dispersed in 10 g of cuprous oxide solution (concentration 10 mg / mL) and stirred for 12 hours to allow the antifouling agent molecules to diffuse into the MOF channels. Centrifugation was performed, and the cuprous oxide adsorbed on the surface was washed with ethanol. The mixture was then vacuum dried at 60°C to obtain the supported zwitterionic functionalized MOF packing.

[0056] Finally, the zwitterionic functionalized MOF zinc acrylate polymer coating was prepared, and the specific process is as follows: Take 350g of zinc acrylate polymer, 50g of supported zwitterionic functionalized MOF material, 200g of xylene, 100g of n-butanol, 100g of light calcium carbonate, 50g of titanium dioxide, 100g of talc, 5g of bentonite, 35g of iron oxide red, 2g of wetting and dispersing agent and 8g of defoamer and put them into a clean reactor in sequence. Stir evenly at 2500r / min and filter after 4h to obtain zwitterionic functionalized MOF zinc acrylate polymer coating for marine antifouling.

[0057] Comparative Example 1: The conventional marine anti-corrosion coating used was H06-1 epoxy anti-rust primer purchased from Liaoning Subote Ship Paint Co., Ltd.

[0058] Comparative Example 2: The preparation process for traditional zinc acrylic antifouling coatings is as follows: Take 300g of zinc acrylate polymer, 150g of xylene, 100g of n-butanol, 60g of zinc oxide, 150g of light calcium carbonate, 60g of titanium dioxide, 150g of talc, 20g of bentonite, 50g of iron oxide red, 5g of wetting and dispersing agent and 5g of defoamer and put them into a clean reactor in sequence. Stir evenly at 2000r / min. After 3 hours, filter to obtain the zinc acrylate polymer coating for marine antifouling.

[0059] Comparative Example 3: The preparation process of the conventional zwitterionic polymer coating for zinc acrylate is as follows: Take 300g of zinc acrylate polymer, 100g of glycidyltrimethylammonium chloride zwitterionic material, 150g of xylene, 100g of n-butanol, 60g of zinc oxide, 100g of light calcium carbonate, 10g of titanium dioxide, 100g of talc, 20g of bentonite, 50g of iron oxide red, 5g of wetting and dispersing agent and 5g of defoamer and put them into a clean reactor in sequence. Stir evenly at 2000r / min and filter after 3h to obtain a conventional zwitterionic compound zinc acrylate polymer coating for marine antifouling.

[0060] Comparative Example 4: The preparation process of the zinc acrylate polymer coating using MOF compound is as follows: Take 300g of zinc acrylate polymer, 100g of UiO-66-NH2, 150g of xylene, 100g of n-butanol, 60g of zinc oxide, 100g of light calcium carbonate, 10g of titanium dioxide, 100g of talc, 20g of bentonite, 50g of iron oxide red, 5g of wetting and dispersing agent and 5g of defoamer and put them into a clean reactor in sequence. Stir evenly at 2000r / min and filter after 3h to obtain MOF compound zinc acrylate polymer coating for marine antifouling.

[0061] Comparative Example 5: The preparation process of the zinc acrylate polymer coating, which is a compound of MOF, zwitterion, and 4,5-dichloro-2-n-octyl-4-isothiazolin-3-one, is as follows: Take 300g of zinc acrylate polymer, 100g of UiO-66-NH2, 50g of 1,4-butanesulfonate lactone, 50g of 4,5-dichloro-2-n-octyl-4-isothiazolin-3-one, 150g of xylene, 150g of n-butanol, 100g of light calcium carbonate, 50g of talc, 10g of bentonite, 40g of iron oxide red, 5g of wetting and dispersing agent, and 5g of defoamer and place them into a clean reactor in sequence. Stir evenly at 2000r / min and filter after 2 hours to obtain a zinc acrylate polymer coating compounded with MOF, zwitterionic acid and 4,5-dichloro-2-n-octyl-4-isothiazolin-3-one for marine antifouling.

[0062] The coatings prepared in Examples 1-6 and the coatings prepared in Comparative Examples 1-5 were subjected to performance testing. The specific test methods and standards are as follows: Adhesion testing was conducted according to the national standard GB / T 9286-2021; Impact resistance performance was tested according to the national standard GB / T 1732-2020; Immersion resistance test: The coatings prepared in Examples 1-6 and the coatings prepared in Comparative Examples 1-4 were applied to steel plates respectively. After drying for 7 days, half of the sample was immersed in seawater and the other half was exposed to air. After immersion for 12 months, the cracking, bubbles, rusting, and color changes of the coating were observed and evaluated. Evaluation criteria: 0-5, with 0 being the best and 5 being the worst. Antimicrobial performance test: Pseudoalteromonas sp., a typical marine fouling bacterium, was used as a model strain for antimicrobial performance testing.

[0063] The coating samples (2 cm × 2 cm) prepared in Examples 1-6 and Comparative Examples 1-4 were placed in a bacterial suspension (10 6 The samples were incubated at 28°C for 24 hours in CFU / mL solution. The samples were then removed and gently rinsed with sterile seawater to remove unattached bacteria. The attached bacteria were then detached by sonication, and the number of viable attached bacteria was determined by plate counting.

[0064] Antifouling performance was tested in accordance with GB / T 5370-2007 at Qingdao Port, Shandong Province, with a test period of 12 months, and the area of ​​biofouling on the hanging plate was observed.

[0065] Antifouling agent sustained-release performance test: The coating prepared in Example 2 and at a physical mixing ratio of 5 was placed in a dialysis bag, immersed in 100 mL of artificial seawater, and allowed to stand at 25 °C for release. 1 mL of sample was taken at regular intervals, and an equal volume of fresh seawater was added. The concentration of DCOIT (4,5-dichloro-N-octyl-4-isothiazolin-3-one) in the released liquid was determined by high performance liquid chromatography (HPLC), and the cumulative release rate was calculated.

[0066] This experiment employed a progressive comparative design, setting up comparative examples 1-4 and a sustained-release comparative sample (comparative example 5) to systematically reveal the core mechanism of action of zwitterionic functionalized MOFs in zinc acrylate resin: Comparative Example 1: Conventional marine anti-corrosion coatings (benchmark control group) Comparative Example 2: Traditional acrylic zinc antifouling coating (basic resin system group) Comparative Example 3: Conventional zwitterionic compounded zinc acrylic polymer coating (physical compounding group I) Comparative Example 4: MOF-based Zinc Acrylic Polymer Coating (Physical Compound Group II) Comparative Example 5: DCOIT antifouling agent physically mixed with zinc acrylic paint (slow-release control group, used only for slow-release testing) Examples 1-6: Zwitterionic functionalized MOF-modified acrylic zinc polymer coatings (chemical functionalization group) Example 2 (DCOIT loaded): Functionalized drug-loaded assembly used for sustained-release performance testing The testing methods cover adhesion, impact resistance, immersion resistance, antibacterial properties, 12-month marine antifouling performance, and antifouling agent slow-release performance, comprehensively evaluating the coating's mechanical properties, media resistance, antibacterial ability, long-term antifouling effect, and antifouling agent controlled release capability.

[0067] The performance test results of Examples 1-6 and Comparative Examples 1-4 are shown in Table 3. Table 3: As shown in Table 3, all samples (Examples 1-6 and Comparative Examples 1-4) exhibited excellent basic mechanical properties. Adhesion was grade 0 (the best grade), no peeling occurred in the cross-cut adhesion test, and impact resistance was ≥50cm (the highest grade). No cracks appeared in the paint film after a heavy hammer impact. This is mainly because the zinc acrylate resin system itself has good film-forming properties and mechanical strength. Whether it was zwitterionic compounding, MOF compounding, or zwitterionic functionalized MOF modification, the basic mechanical properties of the resin were not compromised. This provides a good foundation for subsequent functional improvements.

[0068] In terms of immersion resistance, the differences between chemical functionalization and physical compounding are beginning to emerge. Examples 1-6 and Comparative Examples 3-4 are all at level 0 (no cracking, blistering, rusting or discoloration), while Comparative Examples 1-2 are all at level 1 (with slight defects). The introduction of zwitterions (Comparative Example 3) improved the immersion resistance from level 1 to level 0, proving that the zwitterion hydration layer can effectively inhibit water molecule penetration. The introduction of MOF (Comparative Example 4) also made the immersion resistance reach level 0, which may be related to the binding effect of the nanopores of MOF on water molecules. Examples 1-6 maintained level 0, indicating that chemical functionalization did not destroy this advantage.

[0069] Regarding antibacterial properties, the antibacterial data in Examples 1-6 ranged from 1.9 × 10³ to 3.1 × 10³ CFU / cm², while the antibacterial data in Comparative Examples 1-4 was only 3.8 × 10³ CFU / cm². 4 -7.3×10 5The CFU / cm² of the examples was two orders of magnitude lower (100-fold) than that of the comparative examples. Furthermore, the antibacterial performance of Comparative Example 1 was 8.5 times higher than that of Comparative Example 2 (due to the effect of traditional resin), Comparative Example 2 was 1.7 times higher than that of Comparative Example 3 (due to the effect of physical compounding of zwitterions), and Comparative Example 2 was 2.3 times higher than that of Comparative Example 4 (due to the effect of physical compounding of MOF). The antibacterial performance of Examples 1-6 was 16-27 times higher than that of Comparative Example 3 or 4 (due to the core contribution of chemical functionalization). These results indicate that the physical compounding of zwitterions and MOF (Comparative Examples 3 and 4) can improve antibacterial performance, but the improvement is limited (only 1.7-2.3 times). Only by chemically functionalizing zwitterions to MOF can a breakthrough in antibacterial performance be achieved.

[0070] The results of 12 months of real-sea testing show that the biofouling area in all the examples was less than 1%, reaching the international advanced level. In contrast, the best physical compound group (Comparative Examples 3 and 4) still had a biofouling area of ​​approximately 2.8%, while the traditional acrylic zinc coating (Comparative Example 2) had a biofouling area of ​​7.86%, and the conventional anti-corrosion coating (Comparative Example 1) was almost completely fouled (97%). This gradient data clearly demonstrates that zwitterionic functionalization of MOFs is the key to achieving ultra-low biofouling.

[0071] The slow-release test of the antifouling agent DCOIT revealed the chemical basis for its long-lasting antifouling effect. Example 2 released only 15% within 24 hours, effectively avoiding rapid loss of the antifouling agent in the early stages of coating service and ensuring that the surface always maintains an effective antibacterial concentration. After 30 days, 38% of DCOIT was still retained, meaning that the antifouling agent could be continuously supplied and maintain surface activity during the 12-month marine testing period. In contrast, the physical mixing system (Comparative Example 5) released 45% in 24 hours, meaning that nearly half of the antifouling agent was rapidly lost in the early stages. It released 85% in 7 days and 92% in 30 days, showing a typical burst release + rapid decay curve. This indicates that Comparative Example 5 has a short effective lifespan, with the antifouling agent almost exhausted within one month, failing to meet the requirements for long-lasting antifouling. This further demonstrates the "intelligent controlled release" advantage of chemically functionalized MOFs. The pore confinement effect of MOFs and the synergistic effect of the zwitterionic hydration layer barrier achieve "on-demand release" of the antifouling agent, which is one of the fundamental reasons why Example 2 can maintain a fouling area of ​​<1% throughout the year.

[0072] DCOIT molecules are encapsulated in the regular channels of MOF. Release requires overcoming the diffusion resistance of the channels. Chemically bonded zwitterions form a hydration layer barrier on the MOF surface, which further slows down the diffusion of the antifouling agent. The chemical bonding between zwitterions and MOF may also have a weak interaction with DCOIT, forming molecular-level controlled release. Thus, the MOF channel confinement effect + zwitterion hydration layer barrier = synergistic controlled release effect.

[0073] Therefore, this invention successfully constructed a novel marine antifouling coating with high-efficiency antibacterial properties, intelligent controlled-release capability, and multiple synergistic antifouling mechanisms by chemically modifying zinc acrylate resin with zwitterionic functionalized MOF.

[0074] Antimicrobial test data show that the number of attached viable bacteria in Examples 1-6 (1.9×10³-3.1×10³ CFU / cm²) was significantly lower than that in Comparative Examples 1-4 (3.8×10³ CFU / cm²). 4 -7.3×10 5 The fact that the CFU / cm² is 1-2 orders of magnitude lower directly demonstrates the decisive advantage of chemical functionalization in inhibiting initial microbial attachment.

[0075] The sustained-release test data showed that the functionalized MOF carrier (Example 2) had a release rate of only 62% after 30 days, while the physical mixture (Comparative Example 5) had a release rate as high as 92%. Furthermore, Example 2 effectively suppressed the initial burst release (15% vs 45% at 24 hours), demonstrating the unique advantages of chemically functionalized MOFs as intelligent controlled-release carriers.

[0076] These two micro-mechanisms correspond perfectly with the macro-level 12-month real-world marine pollution prevention data (Examples 1-6 <1% vs. Comparative Example 2-4 2.8%-97%), forming a complete chain of technical evidence.

[0077] The system comparison experiments of Comparative Examples 1-5 proved that simple zwitterionic compounding, MOF compounding, or physical mixing of antifouling agents could not achieve a breakthrough in performance. Only by functionalizing MOF with zwitterionic compounds through chemical bonding (Examples 1-6) could the international advanced level of 384 times improvement in antibacterial activity, 48% reduction in 30-day slow-release rate, and <1% antifouling area after 12 months be achieved.

[0078] Finally, it should be noted that the above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art can still modify the technical solutions described in the foregoing embodiments or make equivalent substitutions for some of the technical features. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the protection scope of the present invention.

Claims

1. A zwitterionic functionalized MOF zinc acrylate polymer coating for marine antifouling, characterized in that, Included by weight Zinc acrylate polymer 30-50 parts, supported zwitterionic functionalized MOF material 5-20 parts, solid filler 20-40 parts, functional additives 1-2 parts, and organic solvent 15-30 parts; The preparation process of the supported zwitterionic functionalized MOF material is as follows: The impregnation adsorption method was used to disperse zwitterionic functionalized MOFs with a mass ratio of 1:5-20 in an antifouling additive solution with a concentration of 1-20 mg / mL, and the mixture was stirred for 6-24 hours to allow the antifouling additive molecules to diffuse into the MOF pores. Centrifugation was performed, and the antifouling agent adsorbed on the surface of the above zwitterionic functionalized MOF was washed with anhydrous solvent. The MOF was then vacuum dried at 60°C to constant weight to obtain the supported zwitterionic functionalized MOF material.

2. The zwitterionic functionalized MOF zinc acrylate polymer coating for marine antifouling as described in claim 1, characterized in that, The zinc acrylate polymer is an acrylic copolymer with zinc ester side chains, having an acid value of 50-200 mg KOH / g and a zinc content of 2-15 wt%.

3. The zwitterionic functionalized MOF zinc acrylate polymer coating for marine antifouling as described in claim 1, characterized in that, The solid filler includes any one or more of titanium dioxide, talc, barium sulfate, heavy calcium carbonate, light calcium carbonate, zinc oxide, mica powder, bentonite, and iron oxide red.

4. The zwitterionic functionalized MOF zinc acrylate polymer coating for marine antifouling as described in claim 1, characterized in that, The functional additives include any one or a combination of wetting and dispersing agents and defoamers.

5. The zwitterionic functionalized MOF zinc acrylate polymer coating for marine antifouling as described in claim 1, characterized in that, The organic solvent includes any one or a combination of more than one of xylene, toluene, ethyl acetate, butyl acetate, and methyl isobutyl ketone.

6. The zwitterionic functionalized MOF zinc acrylate polymer coating for marine antifouling as described in claim 1, characterized in that, The antifouling additive solution is formed by dissolving any one or more of cuprous oxide, copper pyridinethione, zinc pyridinethione, benzisothiazolinone, and 4,5-dichloro-2-n-octyl-4-isothiazolin-3-one in ethanol.

7. The zwitterionic functionalized MOF zinc acrylate polymer coating for marine antifouling as described in claim 1, characterized in that, The preparation process of the zwitterionic functionalized MOF is as follows. Amino-functionalized MOF and zwitterionic reagent are dispersed in anhydrous solvent, wherein the mass ratio of amino-functionalized MOF, zwitterionic reagent and anhydrous solvent is 1:1-10:50-200, and the reaction is carried out at 40-100℃ for 12-48 hours. After the reaction was completed, the mixture was centrifuged, washed thoroughly with anhydrous solvent 3-5 times to remove unreacted reagents, and dried under vacuum at 40-80℃ to obtain zwitterionic functionalized MOFs.

8. The zwitterionic functionalized MOF zinc acrylate polymer coating for marine antifouling according to claim 7, characterized in that, The amino-functionalized MOF includes any one or more of UiO-66-NH2, MIL-101-NH2, and NH2-MIL-125.

9. A method for preparing a zwitterionic functionalized MOF zinc acrylate polymer coating for marine antifouling according to any one of claims 1-8, characterized in that, Includes the following steps: The supported zwitterionic functionalized MOF material, zinc acrylate polymer, organic solvent, solid filler and functional additives are sequentially placed into a reaction vessel and stirred evenly for 2-5 hours, and then filtered to obtain the coating.

Citation Information

Patent Citations

  • A long-lasting antifouling agent supported on a metal-organic framework and its preparation method

    CN115141508B